PENINGKATAN PROFESIONALISME GURU SEKOLAH MENENGAH PERTAMA MELALUI PENGEMBANGAN MUSYAWARAH GURU MATA PELAJARAN: STUDI KUALITATIF DI KOTA LHOKSEUMAWE - Yunitawati Yunitawati; Zahraini Zahraini; Haryuni Haryuni; Marnita Marnita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The gap between the demands of teacher professionalism and classroom practices remains a major challenge at the junior high school level, particularly in curriculum adaptation, technology integration, and collaborative culture among teachers. In this context, the Subject Teacher Consultation Forum (Musyawarah Guru Mata Pelajaran / MGMP) is considered a strategic platform for supporting continuous teacher professional development. This study aims to analyze the role and effectiveness of MGMP in enhancing the professionalism of junior high school teachers in Lhokseumawe City. The study employed a descriptive qualitative approach involving junior high school teachers who actively participated in MGMP activities. Data were collected through in-depth interviews, observations, and documentation, and were analyzed thematically through data reduction, data display, and conclusion drawing. The findings revealed that MGMP contributes to the improvement of teachers’ pedagogical and professional competencies through curriculum review activities, subject-matter discussions, and collaborative preparation of instructional materials. MGMP also supports technology-based instructional innovation through digital training and the sharing of best practices among teachers. In addition, MGMP contributes to teachers’ career development through mentoring in scientific writing and the strengthening of a collaborative work culture. The findings indicate that MGMP functions as a professional learning community that supports the continuous improvement of teachers’ competencies and professional performance, although stronger institutional support is still required. ABSTRAK Kesenjangan antara tuntutan profesionalisme guru dan praktik pembelajaran masih menjadi tantangan di tingkat Sekolah Menengah Pertama (SMP), terutama dalam adaptasi kurikulum, pemanfaatan teknologi, dan budaya kolaborasi antar guru. Dalam konteks tersebut, Musyawarah Guru Mata Pelajaran (MGMP) dipandang sebagai forum strategis untuk mendukung peningkatan kompetensi guru secara berkelanjutan. Penelitian ini bertujuan menganalisis peran dan efektivitas MGMP dalam meningkatkan profesionalisme guru SMP di Kota Lhokseumawe. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek guru SMP yang tergabung dalam MGMP. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis secara tematik melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa MGMP berperan dalam meningkatkan kompetensi pedagogik dan profesional melalui kegiatan bedah kurikulum, diskusi materi, dan penyusunan perangkat pembelajaran secara kolaboratif. MGMP juga mendukung inovasi pembelajaran berbasis teknologi melalui pelatihan digital dan kegiatan berbagi praktik baik antar guru. Selain itu, MGMP berkontribusi terhadap pengembangan karier guru melalui pendampingan penulisan karya ilmiah dan penguatan budaya kerja kolaboratif. Temuan penelitian menunjukkan bahwa MGMP dapat berfungsi sebagai komunitas belajar profesional yang mendukung peningkatan kompetensi dan kinerja guru secara berkelanjutan, meskipun masih memerlukan dukungan institusional yang lebih optimal.